PENGARUH BAURAN PEMASARN (MARKETING MIX) TERHADAP KEPUASAN KONSUMEN - Sunarti Djoko (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2022)
Competition in the increasingly competitive world of marketing requires marketers to continue to give more to consumers in increasing competitiveness. To meet the needs and desires of consumers, one of the business fields that continues to grow is the field of technology and communication, namely smartphone or cellular phone users. With tight business competition, marketing tools such as marketing mix are needed. This study aims to determine the magnitude of the influence of the marketing mix on consumer satisfaction in the city of Ternate. The research method uses a survey with a questionnaire as a data collection tool. Samples were taken using a simple random sampling technique which resulted in 55 respondents. The data were processed using multiple regression analysis techniques. The results showed that: (1) it was empirically proven that product (X1), price (X2), distribution (X3), promotion (X4), and process had a significant effect on customer satisfaction; This means that the better the product, price, distribution, promotion and process, the customer satisfaction will increase. (2). Physical appearance (X5) and People (X6) which are empirically proven have no effect on consumer satisfaction; it means that physical and human appearance has no significant effect on customer satisfaction. Thus, the findings of this study prove that physical appearance (X5) and people (X6) are the main factors in buying a product, but the most important thing is the quality of the product itself which is in accordance with its function. Keywords: Marketing mix, Consumer Satisfaction